ON DEVELOPMENT OF IMPORT-REPLACING PRODUCTION OF ENHANCED FOODSTUFFS FOR THE POPULATION OF NORTHERN REGIONS OF RUSSIA - Shchukin P. O., Vasilyev A. S., Sukhanov I. V. (Science and education: future development, 2018)
in the framework of the implementation of tasks to develop technical and technological solutions for import-substituting production of enriched food products for the population of the Northern Territories of Russia, a set of scientific and research and applied works is carried out.
Keywords: население Севера; population of the north; обогащенные продукты питания; enriched food products; импортозамещающее производство